Hair analysis interpretation in post-mortem situations: Key considerations and proposals to overcome main hurdles. (May 2022) - Benhalima, Ilyes; Castex, Eugénie; Dumont, Guillaume; Gish, Alexandr; Hakim, Florian; Allorge, Delphine; Gaulier, Jean-Michel
Highlights: To address hair results interpertation pitfalls in post-mortem situation To introduce these additional interpretation pitfalls and related consequences To put forward steps or in order to overcome these issues Abstract: In the analytical challenge of post-mortem toxicological investigations of victim's drug history, hair analysis constitutes a useful tool. Nevertheless, in addition to usual limitations of hair result interpretation, there are additional pitfalls in post-mortem situations. This manuscript aims to address post-mortem hair analysis interpretation difficulties and proposals to overcome them. In post-mortem situations, mainly in cases of putrefaction, additional interpretation pitfalls are related to contamination issues consisting in drug incorporation into hair at the time of death (in case of intoxication and excessive sweating) and/or during the post-mortem period by putrefaction fluids. To overcome these issues, conventionally accepted criteria and considerations that must be taken into account encompass knowledge of death circumstances, confidence in analytical results, hair decontamination steps, segmental hair analysis, concentration consideration (values and hair concentration pattern), bath wash analysis results and observed parent drug/metabolites ratio. Nevertheless, none of these proposals is able to formally discriminate positive hair results related to intakes by the victim in the weeks or months before death, from hair contaminations (including those that occurred at the time of death and/or during the post-mortem period). A promising option could be to associate nails analysis to hair ones.